Activin A is an autocrine activator of rat pancreatic stellate cells: potential therapeutic role of follistatin for pancreatic fibrosis. Issue 10 (11th September 2003) - Ohnishi, N; Miyata, T; Ohnishi, H; Yasuda, H; Tamada, K; Ueda, N; Mashima, H; Sugano, K
Abstract : Background and aim: The present study was conducted to examine the effect of activin A on activation of rat pancreatic stellate cells (PSCs). Methods: PSCs were prepared from rat pancreas using collagenase digestion and centrifugation with Nycodenz gradient. Activation of PSCs was examined by determining smooth muscle actin expression with western blotting. The presence of activin A receptors in PSCs was investigated by reverse transcription-polymerase chain reaction (RT-PCR), western blotting, and immunocytochemistry. Expression of activin A and transforming growth factor β (TGF-β) mRNA was examined by RT-PCR. Activin A and TGF-β peptide concentrations were examined with ELISA. Existence of activin A peptide in PSCs was investigated by immunocytochemistry. Collagen secretion was determined by Sirius red dye binding. Results: Activin A receptors I and IIa were present in PSCs. PSCs expressed activin A mRNA and secreted activin A. Activin A enhanced PSC activation and collagen secretion in a dose dependent manner. TGF-β and activin A increased each other's secretion and mRNA expression of PSCs. Follistatin decreased TGF-β mRNA expression and TGF-β secretion of PSCs, and inhibited both PSC activation and collagen secretion. Conclusion: Activin A is an autocrine activator of PSCs. Follistatin can inhibit PSC activation and collagen secretion by blocking autocrined activin A and decreasing TGF-β expression and secretion of PSCs.